Information content of Quarterly Earnings Announcements revisited - BENGHARBIA, DR. SALEM (Dirasat in Economics and Business, 1982)
One major objective of earnings numbers is to provide decision-relevant information objective to users of financial statements that include, among other groups, capital market participants However, the debate over whether earnings reports contain useful information to these groups has been, and still is, a controversial issue. For instance, Ball and brown (1968) provided an early analysis of stock market response to published financial data. Their study supported the efficient market hypothesis (EMH) and indicated that subsequent to earnings announcements, no abnormal return to securities in their sample could be made. A similar conclusion was also obtained by Benston (1973). He argued that studies relating published accounting statement data with stock prices lead to the conclusion that the data either are not useful or have been fully impounded in stock prices before they are published.